2020
DOI: 10.3390/en13226099
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CO2 Concentration on Children’s Well-Being during the Process of Learning

Abstract: There are more than 200 thousand pupils in Latvia. Most of them are still learning in non-renovated classrooms without proper mechanical ventilation. The classrooms are often ventilated only during the breaks by opening windows. This can lead to increased CO2 levels and reduced mental performance. To test how CO2 concentration in classrooms influences student attention level and their ability to perform mental tasks, the students had to complete a short test at the start and the end of the class. At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The tests were performed at a CO2 concentration of 600, 1000, and 2500 ppm. In a recent study [32] it was found that as the CO2 concentration in the classroom increases, the performance test results decrease. Also, some studies [33] indicate that the increase in CO2 concentration can lead to lower attendance levels.…”
Section: Introductionmentioning
confidence: 97%
“…The tests were performed at a CO2 concentration of 600, 1000, and 2500 ppm. In a recent study [32] it was found that as the CO2 concentration in the classroom increases, the performance test results decrease. Also, some studies [33] indicate that the increase in CO2 concentration can lead to lower attendance levels.…”
Section: Introductionmentioning
confidence: 97%
“…The building occupants' satisfaction is also affected by control over the indoor environment, layout, size, aesthetics, and type of HVAC, among others [6,7]. IEQ in higher educational buildings can greatly affect the learning process [8][9][10]. The evidence indicates that their associated facilities have a significant impact on occupants [11].…”
Section: Introductionmentioning
confidence: 99%
“…As reported, the concentration of 222 Rn was increased from 17.5 to 49.6 Bq m −3 (11–33%) [ 36 ] and for 32 Bq m −3 (20%) [ 37 ] right after the building energy renovation. Similarly, the surveys of CO 2 in new and renovated residential [ 39 ] and non-residential buildings [ 33 , 38 ] showed an increase in CO 2 concentrations during occupancy to 2500 ppm [ 33 , 38 ] and 3000 ppm [ 39 ] (approximately 5–6 times, if the initial CO 2 concentration is about 500 ppm). The increased CO 2 concentrations were associated with lower ventilation rates, particularly in younger dwellings [ 40 ] that are naturally [ 40 , 41 , 42 , 43 ] or mechanically ventilated [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, such engineering measures might be related to a deterioration in indoor environmental quality. IAQ in energy-efficient residential and non-residential buildings has already been analysed by many authors [ 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The problem of increased indoor radon concentrations in renovated residential buildings has also been highlighted in several studies [ 32 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%